The Effect of Paddressing and Scanning Training on the Skills of PMR Students in MAN 1 Pohuwato - Pipin Yunus; Haslinda Damansyah; Fandrian Potutu (Universitas Ibn Khaldun Bogor, 2024)
Emergency conditions can occur anywhere and anytime. However, it does not rule out the possibility of emergency conditions occurring in areas that are not covered by health workers. The purpose of this study was to determine the effect of dressing and scanning training on the skills of PMR MAN 1 Pohuwato students. This research method is quantitative research that uses the Two Group Pretest Posttest design. The population in this study was 22 students and the sample was 22 students. From the results of statistical tests on the application of dressing and scanning in the Experimental group of students, a p-value value of 0.003 was obtained, and the control group had a p-value of 1,000. Dressing and scanning training has an influence on students' skills which can be seen from the improvement of students' skills before and after being given dressing and scanning training in the experimental group, while for the control group, there is no change in skills, so it can be concluded that there is an influence of dressing and scanning training on students' skills. Suggestions for schools to conduct splint wrap training to improve students' skills.